Von Willebrand factor, clotting factors, and clotting inhibitors in apheresis platelet concentrates. Issue 3 (23rd June 2013) - Weiss, Dominik R.; Franke, D.; Strasser, Erwin F.; Ringwald, Juergen; Zimmermann, Robert; Eckstein, Reinhold
<x xml:space="preserve">Abstract</x> Background Apheresis platelet concentrates (APCs) are usually stored in citrated plasma at 22°C. The stability of coagulation proteins—von Willebrand factor (vWF), clotting factors (CFs), and their inhibitors—has often been described in association with the storage of thawed plasma. However, fewer data are available regarding changes in APCs. Study Design and Methods We measured CF activities and inhibitors in APCs on the day of manufacture (Day 0) and on Days 4, 5, and 7. vWF was determined by measuring vWF antigen (vWF:Ag) and vWF ristocetin cofactor (vWF:RCo) and by multimer analysis. Results Twenty‐one PCs obtained by plateletpheresis were studied. Major changes were observed for Factor (F)VIII (37% loss of activity within 4 days), FV (20% within 4 days), and protein S (76% within 4 days). All other CF activities remained higher than 80% over the 7 days. Fibrinogen and the inhibitors antithrombin and protein C remained quite stable. FXI, FXII, and FXIII actually increased during storage (8, 11, and 12% within 4 days). vWF:Ag increased during storage of APCs by 2% per day, with a relative loss of vWF:RCo and high‐molecular‐weight multimers. Conclusion Even after 7 days of storage at 22°C, the hemostatic potential of the plasma content in APCs was roughly preserved. The increase in FXII antigen indicates that this CF may also be stored in platelets; however, this has not yet been described.